Facial hyperpigmentation: Any link to cancer? - Deihim, Tina (Adv J Emerg Med, 2018)
INTRODUCTION: Ectopic adrenocorticotropic hormone (ACTH) syndrome is recognized by edema, proximal muscle weakness, hypertension, diabetes and skin hyperpigmentation. This syndrome is mainly associated with malignancies. CASE PRESENTATION: A 43-year-old woman came to our hospital with a history of new-onset diabetes, hypertension, edema and facial hyperpigmentation from four months before. Upon admission, she had alkalosis, hypokalemia, mild hypertension and low-grade fever. Due to abdominal pain, an abdominal ultrasound was performed, which revealed common bile duct (CBD) and pancreatic duct dilation. The abdominopelvic computed tomography (CT) scan showed a poorly-enhancing mass in the periampullary region. CONCLUSION: The patient's facial hyperpigmentation and hypokalemia appear to have been due to ACTH ectopic syndrome as a result of periampullary cancer.